Estudio de factibilidad para elaboración de un módulo para el control de pedidos de la tienda Mr Cell en la ciudad de Babahoyo - Noblecilla Molina, Darwin Jhonatan (2019)
At present, the increase in companies linked to trade has grown significantly, especially in the sales sector, making it essential to develop its own application to establish advantages before the competition, thus streamlining its processes to establish advantages towards competition. The administrator needs to obtain truthful information about what is happening in his company in real time, optimize his processes in stock and prices of products, having as an ally the internet to be able to cover other markets. In the Mr Cell store, the order control is carried out manually, that is, with the use of Kardex, which generates a delay in the ordering, stock review and billing update of the work done in the store. The research line proposed for this feasibility study of the Mr. Cell store in the city of Babahoyo, is oriented to the development of systems, whose line refers to Software Engineering. In this case study the deductive and inductive methodologies are used in which the deductive is the one that starts from the general to the particular with this proposed topic will be studied and an investigation will be carried out of why it still carries out manually the processes of inventories, stock, which are made through the use of Kardex, which generates a delay in ordering, stock review and billing of the work done in the store, while the inductive is the one that starts from the particular to In general, according to the theme, it will be based on observations, behavior analysis and handling of the order module for the store, thus establishing work with real events